Ethnic Innovation and U.S. Multinational Firm Activity - Foley, C. Fritz; Kerr, William R. (Management Science, 2013)
This paper studies the impact that ethnic innovators have on the global activities of U.S. firms by analyzing detailed data on patent applications and on the operations of the foreign affiliates of U.S. multinational firms. The results indicate that increases in the share of a firm's innovation performed by inventors of a particular ethnicity are associated with increases in the share of that firm's affiliate activity in countries related to that ethnicity. Ethnic innovators also appear to facilitate the disintegration of innovative activity across borders and to allow U.S. multinationals to form new affiliates abroad without the support of local joint venture partners. This paper was accepted by Bruno Cassiman, business strategy.